IMPROVEMENT OF SURGICAL TREATMENT METHODS FOR CHRONIC DESTRUCTIVE PERODONTITIS USING OSTEOPLASTIC MATERIALS - Ortikova Nargiza Khairullayevna; Normuratov Lazizjon Azizovich (Western European Studies, 2026)
Chronic destructive periodontitis is a common inflammatory condition affecting the tissues around the tooth roots, leading to the progressive loss of bone and the formation of periapical lesions. Traditional surgical treatments aim to eliminate the source of infection, but they often fail to fully regenerate bone. The use of osteogenic materials in combination with advanced surgical techniques can significantly improve treatment outcomes, promote accelerated bone regeneration, and restore the structure of alveolar bone. This article discusses the principles of using osteogenic materials, compares different treatment approaches, and explores opportunities for further improvement in this area
Keywords: chronic destructive periodontal disease; promote accelerated bone regeneration; osteoplastic substances